STUDENTS' PERCEPTION OF HOAXES AND POLITICAL DISINFORMATION: A DIGITAL LITERACY STUDY IN THE PANCASILA AND CITIZENSHIP EDUCATION STUDY PROGRAM - Heri Ginanjar; Hilmi Nurfaizan; Tetep (Institut Pendidikan Indonesia, 2026)
The proliferation of hoaxes and political disinformation on social media requires students of the Pancasila and Civic Education (PPKn) study program, as prospective educators of civic values, to possess adequate digital literacy and critical thinking skills. This study aims to describe PPKn students' perceptions of hoaxes and political disinformation and to analyze their level of digital literacy in dealing with such information. The study employed a descriptive qualitative approach supported by survey data, using a Likert-scale questionnaire administered to 85 PPKn students and in-depth interviews with 8 selected informants. The findings indicate that PPKn students possess a relatively high conceptual understanding of hoaxes and political disinformation, yet their active information-verification skills remain at a moderate level. The study also found a gap between cognitive awareness and actual behavior in verifying information before sharing it on social media. This study recommends strengthening critical digital literacy content in the PPKn curriculum and cultivating fact-checking habits as part of digital civic education in higher education.